Collagen Fibril Diameter in Relation to Bone Site and to Calcium/Phosphorus Ratio - Panagiotis Berillis; Dimitris Emfietzoglou; Margaret Tzaphlidou (The Scientific World Journal)
The collagen fibril diameter was measured in cortical bone samples from the femoral neck, rear and front tibia of female and male rats and rabbits using electron microscopy analysis. In most cases, statistically significant differences in mean fibril diameter values between different bone sites were detected. The order of magnitude for the above structural parameter was the same for both genders in both experimental species. In rats, the greatest mean diameter value was that for the femoral, while in rabbits, the one for the rear tibia demonstrating a dependence on bone use and life style. An important aspect was the agreement between these observations and the mean values for Ca/P ratio, as observed in previous experiments, in the same bone sites and animals. Collagen fibril diameter and Ca/P ratio can both serve as indexes of bone quality.